The effects of tax administration on tax morale - Werner W. Pommerehne; Bruno S. Frey (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1992)
Econometric analyses of the standard model of tax evasion overwhelmingly reveal that auditing rates and fines do not have the expected, systematic and sizeable deterrence effect on tax evasion. It is shown that tax morale may be the missing factor. In Swiss cantons, characterized by referendum democracy, tax morale seems to be significantly higher than in cantons with representative democracy. As an increase in tax auditing is known to citizen in referendum democracy to undermine tax morale more strongly than in representative democracy, they rationally choose a lower level of auditing than politicians do in a representative democracy; on the other hand, the fines for detected taxpayers are set higher.
Keywords: H26; 330; Steuermoral; Finanzverwaltung; Abstimmungsregel; Schweiz